Effect of scaling and root planing on gingival crevicular fluid level of YKL-40 acute phase protein in chronic periodontitis patients with or without type 2 diabetes mellitus: A clinico-biochemical study - Sini Damodar; Dhoom Singh Mehta (Wolters Kluwer Medknow Publications, 2018)
Background: The aim of the present study was to evaluate the gingival crevicular fluid (GCF) levels of YKL-40 acute phase protein in chronic periodontitis (CP) with and without type 2 diabetes and also to assess the effect of periodontal therapy (scaling and root planing [SRP]) on this GCF biomarker and the clinical parameters. YKL-40 is derived from tyrosine (Y), lysine (K), and leucine (L) with a molecular weight of 40 kDa. Materials and Methods: A total of 105 individuals (30-60 years) were grouped as 35 individuals each in three groups (Group I - healthy; Group II - CP with diabetes mellitus [DM]; and Group III - CP). Clinical parameters including plaque index, gingival index, probing pocket depth, and clinical attachment level followed by GCF sample collection from test sites were done at baseline and 6 weeks after SRP (among Group II and Group III patients). GCF YKL-40 level was determined by enzyme-linked immunosorbent assay. Results: The mean GCF YKL-40 level at baseline was significantly lower for Group I (309.81 ± 124.93 pg/ml) as compared to Group II (924.88 ± 415.28 pg/ml) and Group III (834.08 ± 270.42 pg/ml), respectively (P < 0.001). The level reduced significantly 6 weeks after SRP for Group II (507.6 ± 265.03 pg/ml) and Group III (499.54 ± 293.38 pg/ml) (P < 0.001). Conclusion: The level of GCF YKL-40 in CP patients with or without DM is higher than healthy individuals and the level reduced 6 weeks post-SRP among Group II and Group III. Hence, YKL-40 can be considered as an important biomarker in the diagnosis of CP.